Social Listening as a Public Health Surveillance Sensor: A Comparative Analysis of Vaccine Discourse in Brazil - Moura, Isabela Braga de; Araujo, Claudia (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2026: Anais Estendidos do XXVI Simpósio Brasileiro de Computação Aplicada à Saúde, 2026)
Social listening often assumes that digital signals about different vaccines are interchangeable. This study investigated this assumption by comparing COVID-19, influenza, and HPV vaccine mentions in Brazil (2025) using Meltwater. Analysis of mentions revealed structurally distinct signals: politicized and anger-driven on X for COVID-19; institutional and neutral in online news for influenza; clinical, female-authored, and responsive to awareness months for HPV. Findings demonstrate that social listening captures each vaccine's sociopolitical embedding rather than generic discourse, and that managers should monitor vaccines individually, prioritize engagement over volume, and use platform distribution as an early indicator of signal type.